Molecular Characterization and Functional Analysis of the Nattectin-like Toxin from the Venomous Fish Thalassophryne maculosa - Monica Lopes-Ferreira; Ines Sosa-Rosales; Pedro Ismael Silva Junior; Katia Conceicao; Adolfo Luis Almeida Maleski; Leticia Balan-Lima; Geonildo Rodrigo Disner; Carla Lima (Toxins, 2021)
TmC4-47.2 is a toxin with myotoxic activity found in the venom of Thalassophryne maculosa, a venomous fish commonly found in Latin America whose envenomation produces an injury characterized by delayed neutrophil migration, production of major pro-inflammatory cytokines, and necrosis at the wound site, as well as a specific systemic immune response. However, there are few studies on the protein structure and functions associated with it. Here, the toxin was identified from the crude venom by chromatography and protein purification systems. TmC4-47.2 shows high homology with the Nattectin from Thalassophryne nattereri venom, with 6 cysteines and QPD domain for binding to galactose. We confirm its hemagglutinating and microbicide abilities independent of carbohydrate binding, supporting its classification as a nattectin-like lectin. After performing the characterization of TmC4-47.2, we verified its ability to induce an increase in the rolling and adherence of leukocytes in cremaster post-capillary venules dependent on the α5β1 integrin. Finally, we could observe the inflammatory activity of TmC4-47.2 through the production of IL-6 and eotaxin in the peritoneal cavity with sustained recruitment of eosinophils and neutrophils up to 24 h. Together, our study characterized a nattectin-like protein from T. maculosa, pointing to its role as a molecule involved in the carbohydrate-independent agglutination response and modulation of eosinophilic and neutrophilic inflammation.